Performance of a nitrogen implanted large aperture THz emitter - Świtkowski, Krzysztof Tomasz; Jastrzębski, Cezariusz; Pałka, Norbert; Dyczewski, Jan; Barcz, Adam (Photonics Letters of Poland, 2012)
Improved bandwidth of a large aperture nitrogen implanted GaAs photoconductive THz emitter is presented in this paper. An effect of nitrogen ion implantation on semi-insulating GaAs has been studied in a sample implanted at two doses: 3×1014 and 6×1014 ions/cm2. The carrier life time of the investigated material was measured by means of the femtosecond time-resolved-reflectance technique. The implantation process reduced the carrier lifetime of GaAs by 65%.The bandwidth of the THz emitter was tested in a Time Domain Spectroscopy arrangement. Usable bandwidth of the TDS set-up based on the implanted emitter increased from 1 to 1.5THz. Full Text: PDF References: M.R. Melloch et al., "Low-Temperature Grown III-V Materials", Annu. Rev. Mater. Sci. 25, 547 (1995).CrossRef C. Wang, M. Pocha, J. Morse, M. Singh, B. Davis, "Neutron-treated, ultrafast, photoconductor detectors", Appl. Phys. Lett. 54, 1451 (1989).CrossRef H.H. Tan et al., "Ion-implanted GaAs for subpicosecond optoelectronic applications", IEEE J. Sel. Top. Quantum Electron. 2, 636 (1996).CrossRef P. Kordos, M. Marso, and M. Miculics, "http://dx.doi.org/10.1007/s00339-007-3909-9", Appl. Phys. A, 87 563 (2007).CrossRef W. Shan, K.M. Yu, W. Walukiewicz, J.W. Ager III, E.E. Haller, and M.C. Ridgeway, "Reduction of band-gap energy in GaNAs and AlGaNAs synthesized by N+ implantation ", Appl. Phys. Lett. 75, 1410 (1999).CrossRef A. Patan?, G. Allison, L. Eaves, M. Hopkinson, G. Hill, and A. Ignatov, "Tailoring the electrical conductivity of GaAs by nitrogen incorporation", J. Phys. Condens. Matter 21, 174209 (2009).CrossRef M. Mikulics, M. Marso, P. Kordo, S. Stanek, P. Ková, X. Zheng, S. Wu, and R. Sobolewski, "Ultrafast and highly sensitive photodetectors fabricated on high-energy nitrogen-implanted GaAs", Appl. Phys. Lett. 83, 1719 (2003).CrossRef A.S. Weiling, B.B. Hu, N. M. Froberg, and D.H. Auston, "Generation of tunable narrow?band THz radiation from large aperture photoconducting antennas", Appl. Phys. Lett. 64, 137 (1994).CrossRef S.G. Park, A.M. Weiner, M.R. Melloch, C.W. Siders, J.L.W. Seiders, and A.J. Taylor, "High-power narrow-band terahertz generation using large-aperture photoconductors", IEEE J. Quantum Electron. 35, 1257 (1999).CrossRef F. Ziegler, J.P. Biersack and U. Littmark, The Stopping and Range of Ions in Solids (New York, Pergamon 1985). C.V. Shank et al., "Picosecond time resolved reflectivity of direct gap semiconductors", Solid State Commun. 26, 567 (1978). CrossRef